Strategi Penanggulangan Anak Jalanan Bidang Rehabilitasi Sosial Dinas Sosial Kabupaten Badung - Adnyana, I Made Bagus Dwi Mahatma Sidhi; Tamim, Imron Hadi; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
Street children are a serious problem experienced by children, especially those caught in Badung Regency, the emergence of street children is defined as various reasons for social problems experienced, namely the unfulfilled basic needs properly and adequately. such as protection, affection, education, health, food and shelter. This study aims to describe how the strategy of the Badung Regency Social Service Rehabilitation Division's development program for street children in Badung Regency, as well as to analyze the supporting factors and inhibiting factors that influence the implementation of the street children development program. This study uses a qualitative approach method with a descriptive research type. Data collection techniques through interviews, observation and documentation. In this thesis, the author presents the results of the analysis based on Talcott Parsons theory, namely Structural Functional AGIL is an abbreviation of four important functions needed in a system or strategy in a program, with this the Social Rehabilitation Sector includes the role of Adaptation, namely adjustment to changing conditions, Achieving the main goal of controlling street children is to reduce the number of children living on the streets, Integration, namely coordination between parties, controlling street children requires integration with various parties and, Latency, namely as long-term stability to achieve sustainable control. Keywords : Street children, Social rehabilitation, strategy, Social worker, public